Metafora konseptual dalam naskah mukarramah al-shultan karya kais rakib perspektif john & lakoff - Hasna, Nida Asyfiatul (Maliki Interdisciplinary Journal, 2025)
So far, most researchers in the study of ancient texts have predominantly used a philological linguistic approach in dissecting the content of the text. It is rare to analyze with a literary approach to uncover the secrets in it. This study aims to find the forms of conceptual metaphors from John & Lakoff's perspective in the Mukarramah Al-Shultan manuscript. This type of research is descriptive qualitative research with a hermeneutic approach. The data collection technique uses reading and note-taking techniques. The data analysis technique uses the Miles and Huberman analysis model. The results of the study found 9 forms of metaphor with 3 conceptual metaphor classifications of John & Lakoff's perspective consisting of 3 forms of orientational metaphor, 3 forms of structural metaphor, and 3 forms of ontological metaphor.